2010
DOI: 10.1016/j.hisfam.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Physical stature and biological living standards of girls and young women in the Netherlands, born between 1815 and 1865

Abstract: This is the first study in Dutch anthropometric historiography that describes and analyzes the development of the biological standard of living of girls and young women from the perspective of female adult stature. It is shown that adult stature of women, imprisoned in the second half of the nineteenth century and born between 1815 and 1865, slightly increased, approximately 1 cm. From 1850 onwards stature of women born in the cities notably increased. Development of female adult stature was compared to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Subadults whose growth is retarded may, on completion of growth, fail to reach their genetic potential regarding stature, so, in addition to growth profiles in children, temporal, geographic and other patterning in adult stature has been used by social scientists as a measure of the welfare of modern human groups (Steckel, ). Systematic height surveys began to be undertaken in the 18 th and 19 th centuries AD, very often for the purposes of assessing the health and fitness of military recruits or of prisoners, and these data are an important resource for social historians (e.g., Komlos, ; Padez, ; Bi & Ji, ; de Beer, ). Stature estimated from skeletal remains has been used to extend such studies back into the more remote past (e.g., Bogin & Keep, ; Cardoso & Gomes, 2009; Maat, ), but the majority of biocultural studies of stature using skeletal material are conducted in order to test hypotheses regarding health and nutrition in ancient societies, and how they varied with factors such as social status, subsistence strategy and living conditions (Larsen, : pp.…”
Section: Introductionmentioning
confidence: 99%
“…Subadults whose growth is retarded may, on completion of growth, fail to reach their genetic potential regarding stature, so, in addition to growth profiles in children, temporal, geographic and other patterning in adult stature has been used by social scientists as a measure of the welfare of modern human groups (Steckel, ). Systematic height surveys began to be undertaken in the 18 th and 19 th centuries AD, very often for the purposes of assessing the health and fitness of military recruits or of prisoners, and these data are an important resource for social historians (e.g., Komlos, ; Padez, ; Bi & Ji, ; de Beer, ). Stature estimated from skeletal remains has been used to extend such studies back into the more remote past (e.g., Bogin & Keep, ; Cardoso & Gomes, 2009; Maat, ), but the majority of biocultural studies of stature using skeletal material are conducted in order to test hypotheses regarding health and nutrition in ancient societies, and how they varied with factors such as social status, subsistence strategy and living conditions (Larsen, : pp.…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, Baten and Murray, ‘Heights of men and women’; Carson, ‘Health during industrialization’; de Beer, ‘Physical stature’; Horrell, Meredith, and Oxley, ‘Measuring misery’; Inwood, Maxwell‐Stewart, Oxley, and Stankovich, ‘Growing incomes’. For Belgium: Depauw, ‘Tall farmers and tiny weavers’.…”
mentioning
confidence: 99%
“…Although cultural behaviours are now considerably less detrimental to females, in recent history boys tended to have access to more and better resources, like better nutrition and health care, than their female counterparts. In addition, historically, girls have been exposed to a greater risk for neglect and higher workloads (Cardoso, 2005(Cardoso, /2006, and are also more exposed to infections since girls most often looked after the sick (de Beer, 2010). The sex difference may be related to biological factors.…”
Section: Discussionmentioning
confidence: 99%
“…In height and growth studies, the socioeconomic status of the individuals is usually estimated from indicators of the socioeconomic environment in which they grow and develop. The most common socioeconomic indicators are the income of the families, place of residence, structure and size of the families, occupation and, the educational level of the parents and physical environment (Entwisle and Astone, 1994;Cardoso, 2005Cardoso, /2006Wronka and Pawlińska-Chmara, 2007;Schell et al, 2009;de Beer, 2010). Recently, a study by Komlos (2010) reported stature data from the American population, which includes female data with an emphasis on socioeconomic differences.…”
Section: Introductionmentioning
confidence: 99%